Contextual Learning Strategy: Theoretical Analysis and Implementation of Student-Centered Learning - Mohamad Mahrusillah; Mukhtar Amiruddin Ahmad (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to analyze learning models and teaching methods with a focus on contextual learning strategies and the implementation of Student Centered Learning. Education is understood as a systematic process that not only transfers knowledge but also transforms students’ behavior through the development of cognitive, affective, and psychomotor aspects. This study employs a descriptive qualitative approach using literature and educational document analysis. Classical theories such as nativism, empiricism, convergence, constructivism, operant conditioning, and humanism serve as the foundation for understanding the dynamics of learning. Constructivist theory emphasizes the active role of students in building knowledge, while operant conditioning highlights stimulus-response reinforcement. The findings indicate that Student Centered Learning is relevant in addressing the challenges of modern education, with teachers acting as facilitators, motivators, and innovators. However, research gaps remain in the dominance of normative studies, the limited exploration of affective and psychomotor aspects, and the constraints in adapting classical theories into practice. This study underscores the need for the development of contextual, integrative, and applicative learning models to enhance the quality of human resources holistically.